Juvenile Migraine and Allodynia: Results of a Retrospective Study. Issue 3 (March 2015) - Raieli, Vincenzo; Trapolino, Davide; Giordano, Giuliana; Spitaleri, Chiara; Consolo, Flavia; Santangelo, Giuseppe; Buffa, Daniela; Vanadia, Francesca; D'Amelio, Marco
<x xml:space="preserve">Abstract</x> Background There are only 2 small sample studies investigating allodynia in the pediatric population. The aim of this study was to evaluate the frequency of allodynia during cephalalgic attacks in a juvenile population with primary headaches and its association with other symptoms of migraine. Methods We reviewed all medical records of patients with primary headache consecutively seen during a 2‐year period. Frequency of allodynia was evaluated, by means of a questionnaire, consisting of 6 questions (for example: Do you avoid touching your head when you have a migraine attack?). Results Two hundred thirty children suffering from primary headache were seen during the study period. Two hundred two children were affected by migraine, 28 (12.2%) by other primary headaches. Migraineurs significantly more frequently complained of allodynia compared to other primary headaches (37% vs 0%). At multivariate analysis, allodynia was significantly associated with pain aggravated by physical activity (adjusted odds ratio [ORa ] 2.0, 95% confidence interval [CI] 1.0, 3.8), phonophobia (ORa 2.3, 95% CI 1.0, 5.1), and nausea (ORa 1.9, 95% CI 1.0, 3.7). Conclusion According to our data, allodynia is common during pediatric migraine attacks. The association between allodynia and physical activity, nausea and phonophobia are supported by studies on adult population and suggests specific physiopathological mechanisms.